The E Ffect Of Remuneration And Motivation On Lecturers' Performance With Work Culture As A Moderating Variable In The Faculty Of Pharmacy, University Of Andalas - Defri Hartati; Hendra Lukito; Yulihasri Yulihasri (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
ABSTRACT The ability of state tertiary institutions/state universities to implement the three dharmas of higher education can be used to measure how responsible they are to the minister/central government. In this study, work culture will be used as a moderating variable to assess the impact of compensation and motivation on lecturers' performance at the Andalas University Faculty of Pharmacy. Processing of study data is done using Smart PLS 3.3. Purposive sampling was used in the sampling process, and a total of 43 samples were used. As a result, remuneration has a favorable and noteworthy impact on performancebut does not affect motivation. On the other hand, work culture is able to moderate the effect of remuneration on performance.